1983
DOI: 10.1007/bf01974444
|View full text |Cite
|
Sign up to set email alerts
|

Effect of benomyl on soil fungi associated with rye. 2. Effect on fungi of culm bases and roots

Abstract: The mycoflora of culm bases and roots of rye was assessed in field trials, where benomyl was applied at dose rates ranging from 0.24 to 4.80 kg ha-2. Samples of culm bases were taken three times during the growing season, those of roots only at the harvest date. On culms with various symptoms from untreated plots, Pseudocercosporella herpotrichoides, AIternaria spp. and Gerlachia nivalis were prevalent and on those from benomyl-treated plots Alternaria spp. and Fusarium culmorum. In later stages of growth, G. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The fungicide mixture applied in April 2001, before the oat‐grain inoculum, may have contributed to the greater severity of foot rot in that year by controlling earlier developing pathogens such as eyespot fungi (cf. Bollen et al ., 1983). There is no evidence that seedborne inoculum (encouraged in 1999 and 2000), and hence the presence of pathogen on seedlings, would have contributed more effectively to brown foot rot than did the inoculum applied artificially in spring, had drought‐stress conditions occurred.…”
Section: Discussionmentioning
confidence: 99%
“…The fungicide mixture applied in April 2001, before the oat‐grain inoculum, may have contributed to the greater severity of foot rot in that year by controlling earlier developing pathogens such as eyespot fungi (cf. Bollen et al ., 1983). There is no evidence that seedborne inoculum (encouraged in 1999 and 2000), and hence the presence of pathogen on seedlings, would have contributed more effectively to brown foot rot than did the inoculum applied artificially in spring, had drought‐stress conditions occurred.…”
Section: Discussionmentioning
confidence: 99%
“…A similar reduction in the number of fungal species was observed by Bertoldi et al (1978) and Frahm (1973). Bollen et al (1983) observed that colonization ratio of roots was unaffected but the species composition was still markedly influence by Benomyl. The negative influence that the mycoflora suffers from fungicides has been investigated by a large number of workers (Domsch, 1964(Domsch, , 1970Agnihotri, 1974;Foster, 1975).…”
Section: Effect Of Fungicides On Mycorrhizaementioning
confidence: 95%
“…There was little overall benefit from the fungicide benomyl and this was consistent with a general absence of fungal pathogens. Microdochium bolleyi, which may compete with pathogenic fusaria, is sensitive to benomyl (Bollen et al 1983). Although this was not tested here, the fungus was sensitive to other agrochemicals, including the combination containing benomyl ( Table 5).…”
Section: Dtscussionmentioning
confidence: 99%